Who is the Guardian for Constitutionalism in Europe after the Financial Crisis? - Michelle Everson; Christian Joerges (London School of Economics and Political Science (LSE), European Institute, 2013)
This discussion of the ECJ in the context of a project on political representation in the EU responds to the Court's changing functions in the integration process and also to the critique which the exercise of this function has provoked in recent years after the Court objected to constitutional provisions and legislation of constitutional status in particular in the sphere of labour law and social protection. The ECJ has been accused of partisanship with a neoliberal-monetarist agenda. These debates are bound to extend to the new functions which were assigned to the CJEU in the supervision of the budgetary discipline of Member States in the Euro zone. The problems that might arise in such a case have been foreshadowed by the recent jurisprudence on the legality of the European practices of crisis management. The judgments of the German Bundesverfassungsgericht of 12 September 1212 on the ESM Treaty and the Fiscal Compact and the CJEU Judgment of 27 November 2012 in the Pringle case are of exemplary importance. They document the difficulties both courts have with the defense of the autonomy of law against apparent functional necessities and concurring attitudes in the readiness to accept the primacy of the political.
Keywords: 330